Investigating Teachers Strategies, Model And Media Of Teaching On Post Covid-19 - Mardin Silalahi; Sariaman Gultom; Inggit Arimbi; Nabilah Nisya Milia (Universitas Pahlawan Tuanku Tambusai, 2022)
The aim of this research was to investigate the teachers’ strategy, model, and media of teaching on post covid-19. This research was conducted at SMA SWASTA TAMANSISWA PEMATANG SIANTAR. The approach of research was used in this research by using qualitative research with ethnography method. There are 44 teachers as the subject but only 22 teachers as the sample of this research. The technique of collecting data was observation and interview. The result of this research showed that the strategy which the teacher used in teaching on post covid-19 where cooperative based learning, inquiry based learning, delivery strategy, and management strategy. While, the model of teaching that the teachers used, namely discovery learning, problem based learning, and project based learning. After used the model of teaching, the teachers should be able to design the media of teaching related to their topic or material of subject that will be taught. The media of teaching that the teachers used such as to design videos, power point using image media, and sharing links of video that they found on the internet/google. So, the teachers applied the digital based learning strategy, model, and media of teaching on post covid-19.